1995
DOI: 10.1086/176516
|View full text |Cite
|
Sign up to set email alerts
|

The Central Region in M100: Observations and Modeling

Abstract: We present new high-resolution observations of the center of the late-type spiral M100 (NGC 4321) supplemented by 3D numerical modeling of stellar and gas dynamics, including star formation (SF). NIR imaging has revealed a stellar bar, previously inferred from optical and 21 cm observations, and an ovally-shaped ring-like structure in the plane of the disk. The K isophotes become progressively elongated and skewed to the position angle of the bar (outside and inside the `ring') forming an inner bar-like region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
273
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(305 citation statements)
references
References 55 publications
31
273
1
Order By: Relevance
“…In addition to internal processes (e.g. AGN feedback, Dubois et al 2013;Gürkan et al 2015;Mullaney et al 2015;Bongiorno et al 2016; bar-driven evolution, Knapen et al 1995;Kormendy & Kennicutt 2004;Sheth et al 2005; morphological quenching, Martig et al 2009; virial gas heating, Birnboim & Dekel 2003;Cattaneo et al 2006;Gabor & Davé 2015;etc. ), interactions with local environments play a significant role in shaping the observed properties of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to internal processes (e.g. AGN feedback, Dubois et al 2013;Gürkan et al 2015;Mullaney et al 2015;Bongiorno et al 2016; bar-driven evolution, Knapen et al 1995;Kormendy & Kennicutt 2004;Sheth et al 2005; morphological quenching, Martig et al 2009; virial gas heating, Birnboim & Dekel 2003;Cattaneo et al 2006;Gabor & Davé 2015;etc. ), interactions with local environments play a significant role in shaping the observed properties of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…These dynamical effects have a wide range of consequences on both the gaseous and stellar content of the galaxy: the central bulge-like stellar component gets heated up (Berentzen et al 1998;Fathi & Peletier 2003;Kormendy & Kennicutt 2004;Athanassoula 2005;Berentzen et al 2007), while gas flows from the outer to the inner regions of the galaxy (Combes & Gerin 1985;Combes & Elmegreen 1993;Maciejewski et al 2002;Regan & Teuben 2004;Baba et al 2010;Masters et al 2012;Kubryk et al 2015). As a result, the radial chemical abundance profile initially flattens (Vila-Costas & Edmunds 1992;Martin & Roy 1994;Matteo et al 2013), and the concentration of gas in the centre of the galaxy increases (Knapen et al 1995;Sakamoto et al 1999). The accumulation of gas in the centre eventually triggers an increase in the star formation rate (SFR) (Devereux 1987 shown that this enhanced star formation activity increases the metallicity of the gas in the central region (Friedli et al 1994;Friedli & Benz 1995), thus explaining the origin of the observed break in the slope of the chemical abundance profiles of barred galaxies (Martin & Roy 1995;Roy & Walsh 1997;Considère et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Both theory and observations reveal the importance of inner Lindblad resonances (ILRs) in slowing down the radial gas inflow within the inner kiloparsec of barred galaxies (e.g., Schwarz 1984;Combes & Gerin 1985;Shlosman et al 1989;Athanassoula 1992;Sofue 1991;Kenney et al 1992;Knapen et al 1995aKnapen et al , 1995bJogee 2001;Jogee et al 2001). The resulting concentration of molecular gas leads to the formation of nuclear rings on scales of a few hundred parsecs (e.g., review by Buta & Combes 1996).…”
Section: Introductionmentioning
confidence: 99%